Peningkatan Hasil Belajar Matematika Siswa Kelas X3 SMA Negeri I Pangkalan Kerinci Dengan Menerapkan Metode Penemuan Terbimbing - Risnita ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The aim of the research is to increase the student learning matematics X3 classSMAN 1 Pangkalan Kerinci in the matter of trigonometry with the applicaition of guideddiscovery method. This type of reseach is action research class. The research was carried outon the X3 class SMAN 1 Pangkalan Kerinci and performed in two cycles of planning,implementation of action, observation and reflection. The research data were test result oflearning. The collected data were analyzed descriptively.The result of the research show thatapplication of guided discovery method can increase student learning outcomes. Learningoutcomes of students from cycle I to cycle II has increased 9,38 persen. Based on the researchfindings, it can be concluded that the application of guided discovery method can improvestudent learning outcomes in the matter of trigonometry.